Comparative effectiveness and safety of laser, needle, and “quick fenestrater” in in situ fenestration during thoracic endovascular aortic repair - Wang, Xiaokai; Wu, Jianjin; Zhi, Kangkang; Zou, Sili; Jin, Jie; Bai, Jun; Qu, Lefeng (Frontiers in Cardiovascular Medicine, 2023)
Background Special instruments are needed for the revascularization of aortic branches in in situ fenestration during thoracic endovascular aortic repair (TEVAR). This prospective study compared the effectiveness and safety of three currently used fenestraters: laser, needle, and Quick Fenestrater (QF). Methods In all, 101 patients who underwent TEVAR for aortic disease (dissection, n = 62; aneurysm, n = 16, or ulcer, n = 23) were enrolled. All patients were randomly assigned to three groups: 34 were assigned to laser fenestration, 36 to needle fenestration, and 31 to QF fenestration. The epidemiological data, treatment, imaging findings, and follow-up outcomes were analyzed using data from the medical records. Results The technical success rates of the laser, needle, and QF fenestration groups were 94.1%, 94.4%, and 100% (p > 0.05). After correction of mixed factors such as age and gender, it was showed the average operative time (Laser group: 130.01 ± 9.36 min/ Needle group: 149.80 ± 10.18 min vs. QF group: 101.10 ± 6.75 min, p < 0.001), fluoroscopy time (Laser group: 30.16 ± 9.81 min/ Needle group: 40.20 ± 9.91 min vs. QF group: 19.91 ± 5.42 min, p < 0.001), fenestration time (Laser group 5.50 ± 3.10 min / Needle group 3.50 ± 1.50 min vs. QF group 0.67 ± 0.06 min, p < 0.001), and guide wire passage time after fenestration (Laser group 5.10 ± 1.70 min / Needle group 4.28 ± 1.60 min vs. QF group 0.07 ± 0.01 min, p < 0.001) were all shorter with QF fenestration than with the other two tools. The overall perioperative complication rates of the laser, needle, and QF fenestration groups were 5.9%, 5.6%, and 0% (p > 0.05): One case of sheath thermal injury and one case of vertebral artery ischemia occurred in the laser fenestration group; one case each of access site hematoma and brachial artery thrombosis were reported in the needle fenestration group. 89 (88.1%, 89/101) patients were followed for a median of 12.6 ± 1.6 months. The overall postoperative complication rates of the laser, needle, and QF fenestration groups were 3.3%, 6.5%, and 0% (p > 0.05): In the laser fenestration group, there was one death due to postoperative ST-segment elevation myocardial infarction; in the needle fenestration group, one patient developed occlusion of the bridge stent; no complications occurred in the QF group. Conclusion All three fenestration methods were effective in reconstructing supra-arch artery during TEVAR. QF fenestration required less contrast agent, with a shorter surgery duration and fewer complications than laser and needle fenestration.